Mitopoética na percepção da natureza na aprendizagem Panará - Regina, Adriana Werneck (2013)
The intent of the research is to understand how they are perceived notions of nature and learning from the point of view of the people Panará through the interrelation of mythology with social practices. These people belong to the body language between Ge and inhabits the headwaters Iriri and Peixoto de Azevedo, covering the cities of Guarantã do Norte (MT) and Altamira (PA). The phenomenology of Merleau-Ponty and interpretivism Geertz form the basis of theoretical and methodological understanding of another way to think, feel and act in relation to the world, making the study a translation-oriented cultural otherness in interpretive understanding. Through oral tradition from generation to generation, mythology, in its dynamism, has educational value, working on building a specific view on the stocks of the environment inhabited. Unlike the epistemology of industrial societies, animals and stars are endowed with intent and reflective capacity, positioned as social and interventional, in constant social interaction with people Panará. In this research, it is understood a cosmology in which the animals were active subjects in learning contexts of various skills practiced in daily life. Although the condition does not act more anthropomorphic as possible, their spirits remain in a situation of equivalence with the Panará, so that shamans are those who have the knowledge and power to continue communicating with them. Mythology, finally, assumes relevance in the teaching and learning of this people, and it is engendered by a perception of nature, inscribed in social behaviors, decisive for the environment configuration. The dimension of spirituality witnesses to this perception. This study, therefore, expands the universe of theoretical nature and, in parallel, it is a tool to broaden the conceptual basis of this category in public policy, as well as in public and private projects. Thus, symmetrically legitimizing the knowledge and technical-scientific mythological, incorporating them in building an inclusive society and global hybrid.